IMPLIKASI ADANYA UPAYA HUKUM TERHADAP PUTUSAN BAWASLU TENTANG PELANGGARAN ADMINISTRATIF PEMILU - Ahmad Syarifudin (Universitas Lampung, 2020)
The process of settlement of election administrative of violation’s and implication of the legal remedy mechanism to the Election Supervisory Body (Bawaslu) to Election Supervisory Body Province/District (Bawaslu Kabupaten/Kota) decision that co-create legal uncertainty and losing right to be elected. This is normative law research focus on law norm that related with this topic and using primary legal material Law Number 7 of 2017, Regulation of Election Supervisory Body Number 8 of 2018, Supreme Court Rules Number 4 of 2017 and secondary legal material like book, journal, and research result. Then analyzed with qualitative-juridical are result: First, settlement of election administrative of violation regulated in Article 460 to 465 Law Number 7 of 2017 and Election Supervisory Body Rules Number 8 of 2018. Both regulate settlement of election administrative of violation must implementation open and no later than 14 (fourteen) working days after report received and registred. Second, implication from legal remedy norm to Election Superfisory Body precisely can disturb of the General Election Comission (KPU) working and losing right to use legal remedy to Supreme Court (MA) for candidate who canceled by KPU on the basis of The Election Supervisory Body Provinsi/Kabupaten decision.